Two notes on Proto-Ersuic - Hill, Nathan (My University, 2022)
This paper looks at the history of Tosu using 'forward reconstruction'. It concludes that Proto-Ersuic changed *-im to *-am already before its breakup as a unity, but the ‘brightening’ of *-a- to -i- took place independently in Tosu and Lizu-Ersu. In Tosu this brightening did not target labial (or velar) initial words lacking an inherited medial *-j-. A number of changes in the history of Tosu probably preceded brightening, namely *-um, *-ak > -o and *-u, *-it, *-at, *-ra > -e. In contrast, the change *-e- > -i- in Tosu, of unclear conditioning, appears to be quite late. A dissimilation *CeCe > CeCa is potentially also a recent change.
PUBLISHED
Keywords: Ersu; Lizu; Tosu; historical phonology; forward reconstruction